Interactions Among Same-Status Peers: Effects of Behavioral Style and Status Level. (June 2014) - Spataro, Sandra E.; Pettit, Nathan C.; Sauer, Stephen J.; Lount, Robert B.
When can status peers—group members at the same status level whose relationship can often be characterized by competition and rivalry—experience more harmony than discord? In the current article, we focus on different behavioral styles and status level as joint predictors of interaction among status peers. Specifically, we posit and find that group members' responses to varying behavioral styles exhibited by their status peers shape important group outcomes (i.e., the desire to continue working together and influence accepted from the peer), with the greatest sensitivity to peer behaviors enacted at the highest status levels. Implications for theories of status and influence in groups are discussed.